Synthesis and Biological Evaluation of Iodinated Fidaxomicin Antibiotics. Issue 9 (24th August 2020) - Dorst, Andrea; Shchelik, Inga S.; Schäfle, Daniel; Sander, Peter; Gademann, Karl
Abstract: Fidaxomicin (1, tiacumicin B, lipiarmycin A3) is a marketed antibiotic that is used in the treatment of Clostridium difficile infections. Based on the analysis of a cryo‐EM structure of fidaxomicin binding to its target enzyme (RNA‐polymerase), a cation‐ π interaction of the aromatic moiety with an arginine residue was identified. Therefore, the variation of the substituents and concurrently changing the electronic properties of the aryl moiety represents an interesting strategy in the search for new fidaxomicin analogs. Herein, we report the first semisynthetic access to new fidaxomicin analogs with varying halogen substituents through a Pd‐catalyzed hydrodechlorination reaction. Subsequent iodination gave access to the first iodo‐fidaxomicin derivatives, which matched or improved antibacterial properties compared to fidaxomicin against Mycobacterium tuberculosis and Staphylococcus aureus ATCC 29213. Abstract :